Treading the hallowed halls: women in higher education in India - Chanana, Karuna (2000)
Focusing on the disciplinary choices made by women in higher education and their representation at different levels of learning and teaching, this article goes beyond the issue of women's entry into higher education and raises questions such as: what happens to them after they enter the system? What are the chances of their staying on and progressing from one stage to another? What disciplinary choices do they make? The article also highlights the societal and institutional factors inhibiting women's access to higher education. - Reproduced
Keywords: Higher education - India; Education - India; Womens education - India; Womens education